Religious Moderation: A Critical Discourse Analysis on Rumi’s Thoughts in The Masnavi - Nafisah, Nahdia Ilma (English Literature Study Program, 2022)
This study aimed to reveal the representation of religious moderation that are contained in the poem of Jalal Ad-Din Rumi in his book entitled Masnawi. Rumi is a famous poet who creates beautiful and loves poems, including love in the midst of differences, especially religious diversity, even the Ministry of Religion of Republic of Indonesia was inspired to research deeply about the concept of religious moderation which was initiated by Rumi. Intending to revealing the representation of religious moderation in Rumi's book, the researcher used Critical Discourse Analysis theory which was used to reveal the intentions embedded in discourse, because language is not only reached as a mean of communication, but critically can be understood as a tool that embodies transparent structural relationships of domination, discrimination, power, and control. The CDA theory that is used by the researcher is Wodak’s (2001) theory that well known as the Discourse Historical Approach, by analyzing discursive strategies, discourse practices, and social practices. The finding was Rumi tended to use a predication strategy by attaching positive traits to the moderation discourse and giving negative traits to the opposite, namely extremism and unbalance. His poetry which was widely spread among people from different religions including Islam, Christ and Jew success to convey the message of religious moderation, thus, people understood and applied it well, this is proven by many people mourn on his death. In conclusion, religious moderation was represented as a very positive and good thing in Rumi's poetry in his book entitled Masnawi.